Razão áurea como facilitador no processo de ensino-aprendizagem - Carraro, Jefferson (2021)
The search for conceptualizing and understanding the students’ cognition process and the proposed objectives by Common Core National Standards (Base Nacional Comum Curricular – BNCC) leads to the challenge of using tools that relate the daily routine to mathematical concepts, thus, facilitating the teaching-learning process. The golden mean with the fascination which surrounds it, represented in this research by geometrical constructions, the Fibonacci sequence, the human body, the nature, and the art, can be a facilitator agent in the retention of contents by the students. This study which used the Golden Mean and its constant presence in the human life had as objective to present two didactic sequences that can be extremely relevant tools in the teaching-learning process, making the mathematical knowledge, which is mystified as complex due to its accuracy, more attractive through an easier understanding and better retention of the content by the students during their school lives. After using the proposed sequences, the student should be able to relate the mathematical concepts studied to everyday life.